COMPARATIVE PREDICTIVE VALUE OF THREE PROGNOSTIC MARKERS S-PHASE FRACTION, PCNA AND MITOTIC COUNT ON AXILLARY LYMPH NODE METASTASIS IN CARCINOMA BREAST - Pervez, Shahid; Khan, Muhammad Nadeem; Nasir, Muhammad Israr (Journal of Ayub Medical College Abbottabad, 2007)
Background: Axillary lymph node metastasis is the single most important prognostic factor in carcinoma of the breast. Therefore , prognostic markers that may reliably predict probability of lymph node (LN) metastases are of great value. This study was conducted to compare the predictive value of two novel prognostic / proliferative markers i.e. S-phase fraction (SPF) and proliferating cell nuclear antigen (PCNA) in parallel with mitotic index. Methods: Data of consecutive cases of infiltrating ductal carcinoma (IDC) breast diagnosed from July 2003 to July 2004 at the section of the Histopathology, The Aga Khan University Hospital, Karachi, were reviewed. A total of 112 cases of infiltrating ductal carcinoma (IDC) of the breast with axillary LN sampling were selected. SPF was calculated by flow cytometry while PCNA staining was done by immunohistochemistry. Mitotic count was calculated according to modified Bloom and Richardson's grading guidelines. Result: It was observed that the number of axillary LN metastases was increased with higher SPF (p value: 0.008). However no significant difference was found between the results of various categories of PCNA on axillary LN metastases (p value: 0.182) and mitotic count with axillary lymph node metastases (p value: 0.324). Conclusion: It was concluded that mitotic count and / PCNA alone cannot be used in predicting axillary LN metastases. SPF was found to be a more reliable marker compared to PCNA reactivity and conventional mitotic count in predicting axillary LN metastases. Keyword: S-phase fraction, Proliferating cell nuclear antigen, Mitosis, Axillary Lymph node.